Ideal cardiovascular health at age 5-6 years and cardiometabolic outcomes in preadolescence - Hester Jaspers Faijer-Westerink; Mette Stavnsbo; Barbara A. Hutten; Mai Chinapaw; Tanja G. M. Vrijkotte (BMC, 2021)
Abstract Background The American Heart Association (AHA) developed a definition of ideal cardiovascular health (ICH) based on the presence of both ideal health behaviours (diet, physical activity, weight status and smoking) and ideal health factors (glucose, total cholesterol and blood pressure levels). However, research of ICH in the paediatric population is scarce. We aimed to study ICH at age 5-6 years by extending the original ICH score with the health behaviours: sleep duration, screen time and prenatal smoke exposure, and to evaluate its association with cardiometabolic outcomes at age 11-12. Methods A total of 1666 children aged 5-6 years were selected from the database of the ABCD-study, a prospective cohort study on the health and development of children born in Amsterdam, the Netherlands. Of these, 846 (50.8%) were boys and 1460 (87.6%) had a healthy weight. Data on self-reported health behaviours and health factors were used to calculate the ICH scores (original and extended) by adding the frequency of scoring 'healthy' on each indicator, based on international cut-offs. The children were followed up for 6 years and cardiometabolic outcomes (carotid intima-media thickness (CIMT), blood pressure, glucose and lipids) were measured. Associations between ICH (both original and extended) and cardiometabolic outcomes were examined using multivariable regression models. Results At age 5-6 years, 11% scored poor (score 1-5), 56% intermediate (score 6-7) and 33% good (score 8-9) on extended ICH. Healthy diet and normal total cholesterol concentrations were the least prevalent. Neither the original nor the extended ICH scores were associated with CIMT at age 11-12. A higher score on the extended ICH was associated with lower total cholesterol (p for trend < 0.001), lower systolic (p for trend = 0.012) and diastolic blood pressure (p for trend = 0.011), and lower body mass index (BMI) (p < 0.001) at age 11-12. The original ICH score was associated with lower total cholesterol (p < 0.001) and BMI (p < 0.001) only. Conclusion Our findings suggest that extending the ICH score in young children with additional health behaviours improves prediction of some cardiometabolic outcomes, but not CIMT in preadolescence, compared to the original ICH score. We would recommend other researchers to incorporate objective measures of health behaviours and longer follow-up to find out whether associations persist into adulthood.